Technology of Brown Coal Briquette for High Calorie Alternative Fuel - Jahiding, M.; ., Mashuni; Hasan, E.S.; ., Hajerayani (International Journal of Science, Engineering, and Sustainable Technology (IJSESTech), 2014)
The study of brown coal briquettes quality as an alternative high calorie fuel has been carried out. Briquettes were made using starch, cassava starch, and castor oil plant starch adhesives. Adhesive compositions varied by 5%, 10%, and15% of the total weight of the samples. The size of the powder granules of the brown coal was 0.25 mm (60 meshes). Samples were casted in cylindrical molds with a diameter of 2.5 cm and 6 cm at high compaction pressure of 100 kg/cm2. Coal briquette quality testing covered the parameters of water content, ash content, volatile matter, fixed carbon and calorific value. The results showed that the brown coal briquette with the highest calorific value was obtained in the adhesive composition ratio of 15% for these types of adhesives starch i.e. 4678.68 cal/gram. Adhesives that provide the highest calorific value were that of the starch composing 15%